Design of Mid-Drive Motor Bracket for Electric Bicycles - Harijono, Agus; Mufarrih, AM; Pratama, Rizki Priya; Supriyanto, Nicky Suwandhy Widhi (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2024)
Mid-drive electric bikes have become the favorite choice of many riders thanks to their balanced weight distribution and superior ability to traverse hilly terrain. However, the price of this type of bicycle is still quite high compared to hub drive electric bicycles. This research aims to design an innovative bracket that allows the integration of the hub drive motor from the Ninebot ES into a mid-drive driver. By redesigning this bracket, we hope to improve the bike's performance and efficiency, especially on hills. Bracket design is carried out by considering the dimensions of the motorbike, chainring position, and structural strength to withstand the resulting force and torque. Prototype test results show good stability when driving straight and the ability to reach a maximum speed of 30 km/h on flat roads. Meanwhile, on roads with a slope of 10°, this electric bicycle reaches a maximum speed of 10 km/hour. This bracket design offers an attractive solution for users who want to improve the performance of their electric bike without having to invest in an expensive mid-drive BLDC motor. Further development could involve adding a gearbox to increase torque while reducing motor power consumption. Sepeda listrik mid-drive telah menjadi pilihan favorit banyak pengendara berkat distribusi berat yang seimbang dan kemampuannya yang unggul untuk melintasi medan berbukit. Meskipun demikian, harga sepeda jenis ini masih cukup tinggi dibandingkan sepeda listrik hub drive. Penelitian ini bertujuan untuk merancang bracket inovatif yang memungkinkan integrasi motor hub drive dari Ninebot ES menjadi penggerak mid-drive. Dengan mendesain bracket ini, diharapkan dapat meningkatkan performa dan efisiensi sepeda, terutama pada tanjakan. Perancangan bracket dilakukan dengan mempertimbangkan dimensi motor, posisi chainring, dan kekuatan struktural untuk menahan gaya serta torsi yang dihasilkan. Hasil pengujian prototipe menunjukkan stabilitas yang baik saat melaju lurus dan kemampuan mencapai kecepatan maksimum 30 km/jam di jalan datar. Sedangkan untuk jalan dengan kemiringan 10°, sepeda listrik ini mencapai kecepatan maksimum 10 km/jam. Desain bracket ini menawarkan solusi yang menarik bagi pengguna yang ingin meningkatkan performa sepeda listrik mereka tanpa harus berinvestasi pada motor BLDC mid-drive yang mahal. Pengembangan lebih lanjut dapat menambahkan gearbox untuk meningkatkan torsi sekaligus mengurangi konsumsi daya motor.